DEVELOPMENT OF READING CULTURE OF SCHOOL CHILDREN: RESULTS OF THEORETICAL AND EMPIRICAL RESEARCH - Kachak, Tetiana; Budnyk, Olena; Blyznyuk, Tetyana (Revista Inclusiones, 2020)
The article examines theoretical and practical aspects of the issue of developing school children’s reading culture. The definition of the concept of “reading culture” is generalized, and the factors influencing formation of this type of culture are outlined. Reading is considered to be a creative act, a process of interpersonal communication, a form of cultural participation, acquisition of knowledge, a tool of intellectual and spiritual development of the individual. The structure of reading culture is substantiated, the components of which are: reading competence, literacy, reading interests, reading independence and activity. It has been proved that reading literacy indicates understanding, using, evaluating, comprehending written texts and showing interest in them in order to achieve certain goals, expand knowledge, develop reading potential, readiness for active participation in social life is the core of students’ reading culture. Based on the results of the international assessment of the quality of education PISA-2018, the levels of reading literacy of school children from different countries are compared. Importance of online reading and reading a variety of texts is emphasized. The criteria of reading culture are offered and the level of developmentof this phenomenon in school children is monitored. It was discovered that the majority of the surveyed secondary school students (74.11%) read freely and effortlessly, however, only 22.35% can analyze the work and express critical views on what was read.Search for necessary information becomes motivation to reading for 30.56% of students, whereas 35,3% of respondents enjoy reading, and 12.9% do it under coercion. Individual motivational aspects of reading activity are determined; the best practices of promoting children’s reading in different countries of the world are analyzed